The Outcomes of Health Education Programme on Stress Level Among the Caregivers of Post Total Knee Replacement Surgery - Samsuddin, Md. Fadlisham; Karim, Jalina; Salim, Azizul Akram (Frontiers in Psychiatry, 2021)
Introduction: Stress level among the caregivers is often related to caregivers' lack of knowledge and skill to care for the patients. A health education program to the caregivers is one of the important elements in increasing the knowledge and skills in managing patients at home. The specific objectives of this study were to determine caregiver's stress level in managing post total knee replacement (TKR) patients pre and post of a health education program. Materials and Methods: A clinical intervention trial design was conducted in Hospital Universiti Sains Malaysia (HUSM) with a sample size of 32 caregivers. A validated Zarit Burden Interview (ZBI) questionnaire was used to measure the stress level pre and post of the health education program on the management of patients post-TKR surgery which was adopted from Fresno Surgical Hospital in California. Results: The findings showed that there was a significant difference between pre and post level of stress (p ≤ 0.001). Conclusion: This study revealed the positive outcome of the health education program. It reduced the stress level among the caregivers in caring for their relatives with post-TKR surgery.